Biodiversity in Tomatoes: Is It Reflected in Nutrient Density and Nutritional Yields Under Organic Outdoor Production? - Erika, Cut; Griebel, Stefanie; Naumann, Marcel; Pawelzik, Elke (Frontiers in Plant Science, 2020)
In many regions of the world, human nutrition is still characterized by an insufficient intake of essential nutrients like minerals such as iron (Fe) and zinc (Zn). In view of decreasing resources and a growing world population, the efficiency and sustainability of cultivation systems should be considered not only in terms of crop yield and profit margin, but also in terms of the yield of essential nutrients. Tomatoes are the most consumed vegetable in the world. Organic outdoor tomato cultivation is generally characterized by a higher diversity of varieties and lower fertilization input compared to conventional production. A two-year field experiment with a set of 20 cultivars was performed to evaluate their variation regarding fruit mineral concentrations (potassium [K], calcium [Ca], magnesium [Mg], phosphorous [P], Fe, Zn), their contribution to the dietary reference intake (DRI), and to the nutritional yields (adults ha-1 year-1). Results show that mineral concentrations differed significantly by the cultivar and by the year. Among the cultivars, the contribution of 100 g fresh fruits varied from 4.5% to 7.7% for K, 0.8 % to 1.8% for Ca, 2.3% to 4.4% for Mg, 3% to 6.6% for P, 3.1% to 6.9% for Fe, and 1.9% to 4.2% for Zn to meet daily requirements. Based on average fruit yields per hectare, the cultivars varied with regard to the nutritional yields for all studied minerals, but most strongly for Fe (44 to 120 adults ha-1 year-1) and Zn (22 to 84 adults ha-1 year-1). In terms of contribution to the DRI and nutritional yield for Fe, the cocktail cultivar 'Bartelly F1' produced the highest results, while for Zn the salad cultivar 'Bocati F1' showed the highest values. Our results show that the targeted use of tomato biodiversity in organic outdoor production can be suitable to achieve high fruit yields as well as to produce high nutritional yields per unit area, thus contributing to more effective land use and improved food security.